THE CATION EXCHANGE CAPACITY OF INDUSTRIAL MINERALS AND ROCKS OF MILOS ISLAND - Kantiranis, N.; Filippidis, A.; Vouta, S.; Drakoulis, A.; Koutles, Th.; Tzamos, E. (Bulletin of the Geological Society of Greece, 2007)
Four samples of bentonite, two of perlite, a kaolin and a pumice sample from five mines of Milos Island, have been investigated for their Cation Exchange Capacity (CEC) and the mineralogical composition (wt.%), by using the Ammonium Acetate Saturation (AMAS) method and X-Ray Powder Diffraction (XRPD) method, respectively. The bentonite samples contain 68-100 wt.% clay minerals and show CEC values of 35-121 meq/100g, while the kaolin sample contain 41 wt.% clay minerals and show CEC value of 28 meq/100g. The amorphous materials are the main constituent of the perlite samples (73-77 wt.%) and pumice sample (88 wt.%). The CEC values ofperlites were 3-4 meq/100g, while the pumice sample showed a CEC value of 73 meq/100g. The CEC of the samples showed positive correlations with the total content of microporous minerals (clay minerals+micas) as well as with the microporous minerals+amorphous content, mainly affected by the clay minerals content.